2014
DOI: 10.1016/j.imlet.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence in monocytes, macrophages, and dendritic cells: Lessons learned from the lung and heart

Abstract: In the absence of an immune challenge, healthy, aged individuals have a significantly higher basal inflammatory state where circulating levels of cytokines, including IL-6, TNF-α and IL-1β, are elevated[1]. This progressive pro-inflammatory state, termed “inflamm-aging,” affects the phenotype/function of cells present in the aged as well as renders the older individuals more susceptible to a poor prognosis after systemic insults. Although it is important to understand the mechanisms that underlie the progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 144 publications
(176 reference statements)
1
49
0
2
Order By: Relevance
“…Participants in our cohort exhibited similar ranges of immunosenescence marker levels as observed in other recent studies (13, 5, 14, 51, 52). In our cohort, females had higher TREC levels and higher CD4/CD8 ratios than the male participants, suggesting that the females in our cohort may be less “immunosenescent” than males, as has been previously observed (53, 54).…”
Section: Discussionsupporting
confidence: 85%
“…Participants in our cohort exhibited similar ranges of immunosenescence marker levels as observed in other recent studies (13, 5, 14, 51, 52). In our cohort, females had higher TREC levels and higher CD4/CD8 ratios than the male participants, suggesting that the females in our cohort may be less “immunosenescent” than males, as has been previously observed (53, 54).…”
Section: Discussionsupporting
confidence: 85%
“…ref. ] although they are protagonist immune cells and other experimental methods showed that cardiac macrophages increase during disease .…”
Section: Resultsmentioning
confidence: 99%
“…Monocytes and macrophages cause age‐related deterioration in cytotoxicity, intracellular killing and antigen presentation . Encounter with pathogens results in the activation of macrophages, switching it to a pro‐inflammatory phenotype.…”
Section: Differential Efficiency Of Innate Antiviral Responses In Difmentioning
confidence: 99%